2022
DOI: 10.1002/chem.202200648
|View full text |Cite|
|
Sign up to set email alerts
|

Anomeric Stereoauxiliary Cleavage of the C−N Bond of d‐Glucosamine for the Preparation of Imidazo[1,5‐a]pyridines

Abstract: The targeted cleavage of the C−N bonds of alkyl primary amines in sustainable compounds of biomass according to a metal‐free pathway and the conjunction of nitrogen in the synthesis of imidazo[1,5‐a]pyridines are still highly challenging. Despite tremendous progress in the synthesis of imidazo[1,5‐a]pyridines over the past decade, many of them can still not be efficiently prepared. Herein, we report an anomeric stereoauxiliary approach for the synthesis of a wide range of imidazo[1,5‐a]pyridines after cleaving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Currently, there are no commercial drugs containing this unit, but many studies have demonstrated the potential applicability of imidazo[1,5- a ]pyridines in pharmacology. In Figure 3 , diverse biologically active derivatives of imidazo[1,5- a ]pyridine are depicted, including agonists of cannabinoid receptor type 2 (CB2R) (compound 1 ), serotonin 5-hydroxytryptamine (5-HT4) antagonists (compound 2 ), inhibitors of hypoxia-inducible factor 1α (HIF-1α) (compound 3 ), inhibitors of indoleamine 2,3-dioxygenase (IDO) and tryptophan 2,3-dioxygenase (TDO) (compound 4 ), cribrostatin-6 (compound 5 ), phosphodiesterase 10A inhibitors (compound 6 ), tubulin polymerization inhibitors (compound 7 ), neurokinin antagonists, kinase inhibitors, and various chemotherapeutic agents that have been evaluated [ 65 , 75 , 76 , 87 , 92 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. In addition, in the past, this nucleus has been investigated as a selective, nonsteroidal inhibitor of aromatase for the treatment of estrogen-dependent disease [ 108 ].…”
Section: Studies and Applications Of Imidazopyridine Derivativesmentioning
confidence: 99%
“…Currently, there are no commercial drugs containing this unit, but many studies have demonstrated the potential applicability of imidazo[1,5- a ]pyridines in pharmacology. In Figure 3 , diverse biologically active derivatives of imidazo[1,5- a ]pyridine are depicted, including agonists of cannabinoid receptor type 2 (CB2R) (compound 1 ), serotonin 5-hydroxytryptamine (5-HT4) antagonists (compound 2 ), inhibitors of hypoxia-inducible factor 1α (HIF-1α) (compound 3 ), inhibitors of indoleamine 2,3-dioxygenase (IDO) and tryptophan 2,3-dioxygenase (TDO) (compound 4 ), cribrostatin-6 (compound 5 ), phosphodiesterase 10A inhibitors (compound 6 ), tubulin polymerization inhibitors (compound 7 ), neurokinin antagonists, kinase inhibitors, and various chemotherapeutic agents that have been evaluated [ 65 , 75 , 76 , 87 , 92 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. In addition, in the past, this nucleus has been investigated as a selective, nonsteroidal inhibitor of aromatase for the treatment of estrogen-dependent disease [ 108 ].…”
Section: Studies and Applications Of Imidazopyridine Derivativesmentioning
confidence: 99%
“…The results revealed that amino acids, e.g. glycine 3i (56%) 37 and ( tert -butoxycarbonyl)- l -valine 3h (57%), 38 were noticeably superior to d -glucosamine 3a (27%), 36 1,3,4,6-tetra- O -acetyl-2-amino-2-deoxy-β- d -glucosamine 3b (35%), 27 1,3,4,6-tetra- O -acetyl-2-amino-2-deoxy-α- d -glucosamine 3c (25%), 27 ( S )-diphenyl(pyrrolidin-2-yl)methanol 3d (21%), 39 ( S )-2-(diphenyl((trimethylsilyl)oxy)methyl)pyrrolidine 3e (30%), 39 l -proline 3f (32%), 23 and (5 S )-(−)-5-benzyl-2,2,3-trimethylimidazolidin-4-one 3g (45%). 24 Besides, leucine with d / l - tert -butyl bulk steric hindrance did not obviously affect the reaction activity, such as that of 3j (58%) and 3k (53%).…”
Section: Introductionmentioning
confidence: 99%
“…We propose herewith that a weak-coordination-auxiliary strategy involving an aminocatalyst would help overcome the challenges, especially the energy barrier in the intramolecular cyclization step. With our ongoing interest in the carboxylate assisted activation strategy 31–34 and the preparation of N-heterocyclic compounds by sustainable organic synthesis methods, 27,35,36 herein, we report for the first time glycine-catalyzed [3 + 2] cyclization of α,β-unsaturated ketones and N-heteroaryl ketones for various 2-acylindolizines by a weak-coordination-auxiliary strategy (Scheme 1d).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, available techniques for constructing such a significant motif remain limited. The traditional approaches for synthesizing Im5Py compounds involve a Vilsmeier-type protocol, amination of pyridine followed by 1,3-dipolar cycloaddition, or utilization of excess amounts of activation reagents. , …”
mentioning
confidence: 99%